2011
DOI: 10.4028/www.scientific.net/amr.236-238.173
|View full text |Cite
|
Sign up to set email alerts
|

Sulfite Pretreatment (SPORL) for Robust Enzymatic Saccharification of Corn Stalks

Abstract: This study demonstrates sulfite pretreatment to overcome recalcitrance of lignocellulose (SPORL) for robust bioconversion of corn stalks. With only about 3% sodium bisulfite charge on corn stalks and 30 min pretreatment at temperature 180°C, SPORL can achieve near complete cellulose conversion to glucose in 48h enzymatic hydrolysis. Sulfuric acid charge has great effect on SPORL pretreatment. Enzymatic cellulose conversion of substrate increased with the increase in acid charge under the studied conditions. Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…These results also supported the hypothesis that the inhibitory effect of lignin to enzymatic hydrolysis of cellulose was mainly caused by the non-productive adsorption of cellulase (at low concentration) on lignin through hydrophobic interactions. The observations support the results that the sulfite pretreated biomass had good enzymatic digestibility (Kumar et al, 2011;Wang et al, 2009;Zhu et al, 2009), because the residual lignin in the sulfite- Figure 5. Effect of hydrophilically modified lignin on enzymatic saccharification of cellulose and correlation between drop in the glucose yield at 48 h of cellulose caused by addition of the modified lignin and contact angle of the modified lignin.…”
Section: Correlation Between Hydrophobicity and Inhibitory Effect Of supporting
confidence: 87%
“…These results also supported the hypothesis that the inhibitory effect of lignin to enzymatic hydrolysis of cellulose was mainly caused by the non-productive adsorption of cellulase (at low concentration) on lignin through hydrophobic interactions. The observations support the results that the sulfite pretreated biomass had good enzymatic digestibility (Kumar et al, 2011;Wang et al, 2009;Zhu et al, 2009), because the residual lignin in the sulfite- Figure 5. Effect of hydrophilically modified lignin on enzymatic saccharification of cellulose and correlation between drop in the glucose yield at 48 h of cellulose caused by addition of the modified lignin and contact angle of the modified lignin.…”
Section: Correlation Between Hydrophobicity and Inhibitory Effect Of supporting
confidence: 87%
“…Previous studies have shown that bisulfite pretreatment is an efficient pretreatment, exhibiting great enzymatic cellulose conversion and ethanol production (Tan et al 2013;Tian et al 2011;Wang et al 2011). In the present study, such a process was selected for the CS pretreatment, after which CS was separated into the cellulosic solids and spent liquor.…”
Section: Bisulfite Pretreatment Of Csmentioning
confidence: 99%
“…It has been found that NaHSO3 dosage and H2SO4 dosage are the important factors affecting the bisulfite pretreatment (Tan et al 2016). Previous studies have shown that 1% acid almost completely removes the xylan in the raw material (Tan et al 2013;Wang et al 2011). Therefore, the effect of NaHSO3 dosage was investigated relative to bisulfite pretreatment of CS.…”
Section: Bisulfite Pretreatment Of Csmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore it is urgent to find approaches to efficiently detect food additives. For example sulfite which is very harmful has been extensively applied in different food processing steps such as preservation of fresh fruits, bacterial inhibition and oxidation resistance in the manufacture process of wines such as grape wine and browning prevention of aquatic products [1][2][3][4][5].To change the status of food safety, technologies for detecting food additives have become the key research subject in food safety field [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%